(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
congenital heart defects (CHDs) are the most common types of birth defects, and babies born with these conditions are living longer and healthier lives. Find more statistics about CHDs below. CHDs affect nearly 1% of―or about 40,000―births per year in the United States. The prevalence (the number of babies born with heart defect compared to the total number of births) of some CHDs, especially mild types, is increasing, while the prevalence of other types has remained stable. The most common type of heart defect is a ventricular septal defect (VSD). About 1 in 4 babies with a CHD have a critical CHD. Infants with critical CHDs generally need surgery or other procedures in their first year of life. The prevalence of all types of CHDs, including critical CHDs, varies by state and by type of defect.